Existential attitudes and occupational burnout syndrome in nurses - Mazur, Anna; Goś, Anna; Humeniuk, Ewa (Nursing in the 21st Century, 2017)
EXISTENTIAL ATTITUDES AND OCCUPATIONAL BURNOUT SYNDROME IN NURSESAim. The aim of the study was to determine the relation between existential attitudes and occupational burnout in nurses.Material and methods. The research sample consisted of 120 nurses. Life Attitudes Profile – Revised (the LAP-R) adapted by R. Klamut and Link Burnout Questionnaire (the LBQ) adapted by A. Jaworowska were used in the research.Results. Psycho-physical exhaustion and relationship deterioration correlate negatively with life goals, internal consistency, life control, death acceptance and positively with existential void and goal seeking. Sense of professional failure and disillusion present a conversely proportional relation with goal, coherence, life control as well as an inversely proportional relation with existential void and goal seeking.Conclusions. The analyses performed in the course of the research proved that existential attitudes accompany burnout in nurses. The obtained results of the authors’ own research present cognitive value and can be used to develop both prevention and aid programs aimed at enhancing the quality of personal and professional functioning of nurses.